14 and 11
let x be the second number then the first number = x + 3 ( 3 more than second)
Also 3(x + 3) = 5x - 13
3x + 9 = 5x - 13
subtract 3x from both sides
9 = 5x - 3x - 13
9 = 2x - 13
add 13 to both sides
22 = 2x
divide both sides by 2
11 = x → second number
first number = x + 3 = 11 + 3 = 14
Answer:
its 12 its 12
Step-by-step explanation:
1. 5x+ 2(x+6)
= 5x+ 2x+ 2*6 (distributive property)
= 5x+ 2x+ 12
= (5x+ 2x)+ 12 (combine like terms)
= 7x+ 12
The correct answer is C. 7x+12~
2. <span> -3m + 3(m + 6)
= -3m+ 3m+ 3*6
= -3m+ 3m+ 18
= (-3m+ 3m)+ 18
= 18
The correct answer is D. 18~</span>
Answer:
breadth = 10 cm
length = 13 cm
Step-by-step explanation:
so,
perimeter = 46cm
2(l+b) = 46cm
or, 2(3+b+b) = 46cm ( because l = 3+b)
or, 2(3+2b) = 46cm
or, 6 + 4b = 46cm
or, 4b = 46cm - 6
or, 4b = 40cm
or, b = 40/4 cm
so, b = 10 cm
now,
l = 3cm + b
l = 3 cm + 10cm
= 13cm